A novel Trypanosoma cruzi protein associated to the flagellar pocket of replicative stages and involved in parasite growth - Durante, Ignacio Miguel (2015)
The flagellar pocket constitutes an active and strategic site in the body of trypanosomatids (i.e. parasitic protozoa that cause important human and/or livestock diseases), which participates in several important processes such as cell polarity, morphogenesis and replication. Most importantly, the flagellar pocket is the unique site of surface protein export and nutrient uptake in trypanosomatids, and thus constitutes a key portal for the interaction with the host. In this work, we identified and characterized a novel Trypanosoma cruzi protein, termed TCLP 1, that accumulates at the flagellar pocket area of parasite replicative forms, as revealed by biochemical, immuno-cytochemistry and electron microscopy techniques. Different in silicoanalyses revealed that TCLP 1 is the founding member of a family of chimeric molecules restricted to trypanosomatids bearing, in addition to eukaryotic ubiquitin-like and protein-protein interacting domains, a motif displaying significant structural homology to bacterial multi-cargo chaperones involved in the secretion of virulence factors. Using the fidelity of an homologous expression system we confirmed TCLP 1 sub-cellular distribution and showed that TCLP 1-over-expressing parasites display impaired survival and accelerated progression to late stationary phase under starvation conditions. The reduced endocytic capacity of TCLP 1-over-expressors likely underlies (at least in part) this growth phenotype. TCLP 1 is involved in the uptake of extracellular macromolecules required for nutrition and hence in T. cruzi growth. Due to the bacterial origin, sub-cellular distribution and putative function(s), we propose TCLP 1 and related orthologs in trypanosomatids as appealing therapeutic targets for intervention against these health-threatening parasites.